Holocene molluscan successions from southeastern Spain (Galera, Andalusia): a palaeoenvironmental framework and a palaeobiogeographic resource of the Granada UNESCO Geopark. (12th January 2023) - Wackenheim, Quentin; Richter, Christiane; Limondin-Lozouet, Nicole; Wolf, Daniel; García-Tortosa, Francisco Juan; Marzin, Elisa; Hofmann, Luise; Dabkowski, Julie; Faust, Dominik
ABSTRACT: In Spain, Holocene deposits are widespread, and although they have been extensively investigated by quaternarists for several decades, their malacological content has remained scarcely studied. In the framework of a German–French–Spanish collaboration, alluvial and tufa sequences in the Baza Basin, Andalusia, Spain are analysed with a multidisciplinary approach, including the analysis of the molluscan successions. Holocene fossil molluscs of the studied sequences reveal a rich assemblage of 53 species, among which 33 are terrestrial. Between 10, 000 and 9, 000 cal. yr BP, the Galera succession indicates strong river dynamics that prevented the establishment of adjacent terrestrial habitats. The Early to Middle Holocene transition reflects the continuity of humid environments. The Middle Holocene fauna reveals a decrease in humidity accompanied by slight evidence of drier habitats in the near periphery of the floodplain/tufa deposits from 5, 900 cal. yr BP onwards. Late Holocene deposits (around 3, 000 to 300 cal. yr BP) point to dry and open biotopes indicated by the appearance of xero-resistant and mesophilous gastropods. The palaeoenvironmental reconstruction inferred from the malacocenoses allows discussing local to regional responses of the malacofauna to environmental changes and is consistent with past regional environmental and climatic trends identified in southeastern Spain. The fossil record at Galera offers new evidence to question and clarify the modern range of endemic taxa whose distributions are fragmented. By following a 'conservation paleobiology' approach, the analysis of the mollusc fossil record at Galera provides (1) baselines to determine the natural variability of ecosystems and their response to environmental changes, (2) data to discuss and clarify species distribution evolution and (3) arguments to support conservation priorities.